Human-Computer Interaction INTERACT ’97 1997
DOI: 10.1007/978-0-387-35175-9_70
|View full text |Cite
|
Sign up to set email alerts
|

Speech timing prediction in multimodal human-computer interaction

Abstract: This paper proposes a quantitative model of natural modality integration for speech and pointinggestures. An experiment is described that study temporal synchronization between speech and pointing gestures during multimodal interaction. The end of a pointing gesture (MT) is shown to be synchronized with either the key word of an expression or the deictic marker of a deictic expression. It is also shown that MT tends to be slightly behind the beginning of its associated word; this tendency becoming more marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…But all the proposed models are essentially of a qualitative nature. Moreover, very few studies have been done in the Human-Computer Interaction (HCI) domain [1] [3].…”
Section: Introductionmentioning
confidence: 99%
“…But all the proposed models are essentially of a qualitative nature. Moreover, very few studies have been done in the Human-Computer Interaction (HCI) domain [1] [3].…”
Section: Introductionmentioning
confidence: 99%
“…This does not necessarily mean that there will be no overlap in performance, e.g. it is possible that someone can begin to move the cursor on a drawing package and then speak a command before the cursor has reached its end-point (Bourguet & Ando, 1997). However, it does mean that MHCI is not simply a matter of combining two or more &unimodal' unit-tasks.…”
Section: Discussionmentioning
confidence: 94%
“…For example, timing information from 3D hand pointing gestures has been used to automatically detect recognition errors in speech [53] [54]. Experimental studies have shown that, during speech and gesture multimodal interaction, 3D hand pointing gestures tend to be synchronised with either the nominal or the deictic ("this", "that", "here", etc.)…”
Section: Automatic Detectionmentioning
confidence: 99%
“…In [54], it is shown that the use of a speech and hand gestures synchronisation model can result in the recovery of up to a third of speech recognition errors.…”
Section: Automatic Detectionmentioning
confidence: 99%